Respuesta :
Answer:
x = 5±sqrt(26)
Step-by-step explanation:
x^2-10x=1
Take the coefficient of x
-10
Divide by 2
-10/2 = -5
Square it
(-5)^2 = 25
Add this to both side
x^2-10x+25=1+25
(x-5)^2 = 26
Take the square root of each side
sqrt((x-5)^2) = ±sqrt(26)
x-5 = ±sqrt(26)
Add 5 to each side
x = 5±sqrt(26)
Answer:
-0.0990195 and 10.09902
Step-by-step explanation:
To complete the square, the same value needs to be added to both sides
x^2-10x+?=1+?
To complete the square x^2-10x+25=(x-5)^2 add 25 to the expression.
x^2-10x+25=1+?
Since 25 was added to the left-side, you need to add it to the right-side as well.
x^2-10x+25=1+25
use a^2-2ab+b^2=(a-b)^2 to factor this expression.
(x-5)^2=1+25
Then add the numbers together.
(x-5)^2=26
Solve for x.
x1=-squareroot26+5
x2=squareroot26+5
therefore you have 2 solutions
x1=-squareroot26+5
=-0.0990195
and
x2=squareroot26+5
=10.09902